The development of Artificial Intelligence in future technology - Sharobidinov Nurmuhamad Nasirullo O`gli (Peerian Journals Publishing, 2022)
Artificial Intelligence(AI) is the lore and engineering of making intelligent machines, purposeof AI providing machines with the ability to think, reach, and surpass human-level intelligence and fast think , solve , judge on problems ,daily life ,industry, experiments, medicines and etc.. in this article we begin with an introduction to the popular field of artificial intelligence, then progress to the emersion, history and the devolop of artificial intelligence. We then consider the main streams in the field, along with the advancement, evolution and it’s applications for various affect of our life. The paper will cover current research related to artificial intelligence, including reinforcement learning, robotics, computer vision, automation and symbolic logic. In addition to this, we highlight the unique advantages for future technologiesand humanity, focusing on opportunities, limitations, and ethical questions. so conclude, we describe several current areas of research within the field and recommendations and advises for future research.
Keywords: Artificial Intelligence; Machine Learning; Deep Learning; Generative Adversarial Networks